2000
DOI: 10.1172/jci9307
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related survival differences in murine cardiomyopathy are associated with differences in TNF-receptor expression

Abstract: IntroductionEpidemiologic studies have observed important differences in survival between men and women with heart failure (1-5). For example, the population-based Framingham Heart Study found that after the onset of symptomatic heart failure, the prognosis of women was significantly better than men (3,4). Similar observations were reported in patients with advanced heart failure, and these sex-related differences could not be attributed to a high incidence of coronary disease in men (1, 2). Furthermore, hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 28 publications
13
95
0
Order By: Relevance
“…In our studies, we observed that DCM developed in both female and male mutant mice, but mortality was more pronounced in male mice than females. This is in accordance with previous studies showing that female sex protects against the severity and frequency of DCM [36,37]. Many studies in a number of mouse strains revealed multiple differences between male and female animals.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our studies, we observed that DCM developed in both female and male mutant mice, but mortality was more pronounced in male mice than females. This is in accordance with previous studies showing that female sex protects against the severity and frequency of DCM [36,37]. Many studies in a number of mouse strains revealed multiple differences between male and female animals.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies in a number of mouse strains revealed multiple differences between male and female animals. Transgenic overexpression of phospholamban, TNF-a, b2AR, NCX showed a gender-related discrepancy in the cardiac phenotype in which the more severe phenotype was observed in males [38][39][40][41]. Similarly, gene disruption of FKBP12.6, phospholamban, and ERa revealed a cardiac phenotype with male preponderance [42][43][44].…”
Section: Discussionmentioning
confidence: 97%
“…TNFR1 is expressed in nearly all cell types (except erythrocytes), while TNFR2 is found primarily in cells of the immune system and myocardial cells. 28,29) Previous research suggests TNFR1/2 signaling is complex; TNFR1 could aggravate while TNFR2 ameliorates chamber remodeling and hypertrophy due to their different effects on NF-kB, JNK, inflammatory activation, and apoptosis. 30) In our study, we compared inflammatory expression in different groups.…”
Section: Discussionmentioning
confidence: 99%
“…Male death rate reaches Ϸ50% by 20 weeks of age, compared with 4% in females. 89 The potential mechanism of this sex difference may be related to elevated circulating levels of TNF-␣ in postmenopausal women. 90 In a recent study, estrogen replacement in ovariectomized rats decreases circulating TNF-␣ after ischemia/reperfusion injury, with a concomitant decrease in TNF receptor 2 and increase in TNF receptor 1.…”
Section: Transgenic Models Targeting Signaling Pathwaysmentioning
confidence: 99%